Risco familiar de crianças atendidas na rede de atenção primária à saúde - Pereira, Fernanda Portela (2016)
Research that aimed to analyze the familial risk of children enrolled in primary health care (PHC) two municipalities. This is a transversal study with a quantitative approach, derived from the multicenter research project entitled "Children with special health care needs in primary care service in health: prevalence and access", approved by the Ethics Committee of the Federal University of Santa Maria (UFSM), under number: 32608114.2.0000.5346. The setting was the network of PHC municipalities Santa Maria / RS and Ribeirão Preto / SP and enrolled in the study 407 family caregivers of children. For the data collection was used questionnaire with variables related to demographics, social and economic aspects of children and their families, Screening Instrument of Children with Special Healthcare Needs (CSHCN) and questions inspired by the Family Risk Scale of Coelho-Savassi (FRS-CS). Data entered into Excel® through independent double typing, after checking for errors and inconsistencies in the Epi info program were analyzed using SPSS version 16.0-Statistics program. The descriptive analysis of the data was presented by absolute and relative frequencies to characterize the children, their primary caregivers and economic condition of the family. And the bivariate analysis using the scale risk scores and the sociodemographic and clinical variables with a significance level of p <0.05, with 95% confidence interval. Presents the Family Risk (FR) general and categorized as lower risk, average and maximum, as the scores set out in the FRS-CS, and classified and Biological and Social Risk (BioSoc): biohazardous (Bio), social (Soc) and both combined (Bio + Soc), as the sentries presented by the family. Prevailed children female, white, attends school part-turn, 29% have some special healthcare needs (SHN), 27% has been hospitalized, 71.3% only uses the National Health System, 97.3% held prenatal care, 50.6% were born by cesarean section. As the primary caregiver, the mother prevailed, white, middle-level education, 58.5% of households in economy class C and 19.4% receive government assistance. The FR percentage in the municipalities was 28.7%, being lower in Ribeirão Preto municipality that has the highest PHC coverage. Association tests variables were significant only for Health System and FR and Health System and BioSoc risk. In both municipalities was high Soc risk percentage (34.9%). The RF was higher for children who have been hospitalized who had problems at birth, with higher risk percentage Bio + Soc, and only use National Health System, high Soc risk percentage. The CSHCN had higher FR, average and maximum risk and Bio risk in relation to non SHN. The FR was higher for children whose primary caregiver has less education, aged between 15 and 19, lower income and who receive government assistance with high risk Soc. The strong social component of risk suggests that the economic and environmental conditions interfere with the FR of children attending by Primary Health Care.